Detection of Transfusion Transmitted Virus (Ttv) Dna By Polymerase Chain Reaction (Pcr) in Patients With Chronic Hepatitis B and Hepatitis C Virus - Toroman, Zülal Aşcı; Bulut, Yasemin; Özdarandeli, Aykut; Kalkan, Ahmet (Fırat University, 2003)
Aim: In the presence of this study, prevalance of transfusion transmitted virus (TTV) was determined by polymerase chain reaction (PCR) in patients with chronic hepatitis B and hepatitis C infection. Materials and method: Forty five chronic hepatitis B and 35 chronic hepatitis C patients included this study. Fifty healthy person were also analysed as a control group. The samples were subjected to proteinase K digestion and phenol-cloroform extraction. Then, semi-nested PCR was performed with TTV spesific primers. The PCR products were run on 2% agarose gel. Results: TTV DNA was present in 9 of 45 (20%) patients with chronic hepatitis B infection, whereas TTV DNA was detected in 11 of 35 (31,4%) patients with chronic hepatitis C infection. 5 (10 %) healthy person was also infected with TTV. Conclusion: Our results indicated that TTV DNA was detected more frequently in patients with chronic hepatitis C infection than in patients with chronic hepatitis B infection. Interestingly, TTV prevalance was high in healthy person group.

Amaç: Bu çalışmada, kronik hepatit B virus (HBV) ve hepatit C virus (HCV) infeksiyonlu olgularda, polimeraz zincir reaksiyonu (PZR) yöntemiyle Transfusion Transmitted Virus (TTV) pozitifliğinin belirlenmesi amaçlanmıştır. Gereç ve yöntem: Çalışmaya, 45 kronik hepatit B ve 35 kronik hepatit C hastası olmak üzere toplam 80 hasta ve sağlıklı 50 birey dahil edildi. Proteinaz K enzimiyle sindirim ve fenol-kloroform ektraksiyonunu takiben elde edilen DNA'lardan TT virus primerleriyle semi-nested PZR yapıldı. Pozitif örnekler % 2'lik agaroz jelde elektroforez sonrası görüntülendi. Bulgular: Toplam 45 kronik hepatit B hastasından 9'unda (% 20) ve 35 kronik hepatit C hastasından 11'inde (% 31.4) ve 50 sağlıklı bireyin ise 5'inde (%10) TTV pozitifliği saptandı. Sonuç: Sonuçlarımız, TTV-DNA'sının, kronik hepatit C'li hastalarda kronik hepatit B'li hastalara göre daha yüksek olduğunu göstermektedir. Ayrıca, TTV DNA pozitifliği sağlıklı insan grubunda da yüksek bulunmuştur.
Kronik Hepatit B ve C Virus İnfeksiyonlu Olgularda Transfusion Transmitted Virus (Ttv) Dna'sının Pzr ile Belirlenmesi